Abuse Potential of Samidorphan: A Phase I, Oxycodone‐, Pentazocine‐, Naltrexone‐, and Placebo‐Controlled Study. (26th November 2018) - Pathak, Sanjeev; Vince, Bradley; Kelsh, Debra; Setnik, Beatrice; Nangia, Narinder; DiPetrillo, Lauren; Puhl, Matthew D.; Sun, Lei; Stanford, Arielle D.; Ehrich, Elliot
Abstract: Samidorphan is a μ‐opioid receptor antagonist in development for the treatment of schizophrenia, in combination with olanzapine, and major depressive disorder, in combination with buprenorphine, at proposed therapeutic doses of samidorphan 10 mg and 2 mg, respectively. A double‐blind, double‐dummy, active‐ and placebo‐controlled, crossover study evaluated the abuse potential of samidorphan in healthy, nondependent, recreational opioid users. Following a qualification phase, participants were randomized to 1 of 6 treatment sequences of study drugs: placebo, samidorphan (10 or 30 mg), oxycodone (40 mg), pentazocine (30 mg), and naltrexone (100 mg) in a 6 × 6 Williams design. The primary end point was maximum effect (Emax ) for "at‐the‐moment" Drug Liking visual analog scale scores. Secondary end points included Emax visual analog scale scores for Take Drug Again and Overall Drug Liking and safety assessments. Among 47 participants, at‐the‐moment Emax Drug Liking scores for positive study controls oxycodone and pentazocine were significantly higher than placebo ( P < .001) and samidorphan (both doses; P < .001). Both samidorphan doses had Emax Drug Liking scores similar to placebo and naltrexone (median within‐subject differences of 0.0). Emax Take Drug Again scores for samidorphan (both doses) were higher than placebo, but similar to naltrexone, an unscheduled μ‐opioid receptor antagonist. Adverse events to evaluate abuse potential occurred less frequently with samidorphan, naltrexone, and placebo than with oxycodone and pentazocine. Findings from this study support a lack of abuse potential with samidorphan at doses up to 30 mg and a safety profile consistent with previous samidorphan clinical studies.